Probing solvent fluctuations in deep eutectic solvents: Influence of probe charge and nano-domain localization - Chowdhury, Tubai; Pathania, Akhil; Ravindranathan, Sapna; Bagchi, Sayan (Journal of Chemical Physics, 2025)
Deep eutectic solvents (DESs) segregate into hydrogen bond acceptor or hydrogen bond donor (HBD) rich nano-domains, leading to molecular heterogeneity. Understanding how this heterogeneity affects the DES structure and dynamics is essential. In this study, we used two-dimensional nuclear magnetic resonance (2D NMR) and two dimensional infrared (2D IR) spectroscopies, combined with molecular dynamics (MD) simulations, to investigate solvation structure and dynamics in two choline chloride-based DESs with different HBDs-levulinic acid and glycolic acid. We introduced two thiocyanate vibrational probes, methyl thiocyanate (CH3SCN, neutral) and ammonium thiocyanate (NH4SCN, anionic), which selectively localize in specific nano-domains. 2D NMR provided insights into solvent structure and probe location, while 2D IR captured solvation dynamics. Our results show that these small probes do not alter the solvent structure, regardless of charge. However, solvation dynamics depend on long-range electrostatic ordering in the DES and the local shielding effects of the nano-domain where the probe resides. MD simulations complement experimental findings, providing a molecular-level understanding of solvation in DESs.